AHP based decision-making in concept selection of keyless grill locking system - Subramonian, Sivarao; Abdul Rahim, Samsudin; Tan, C. F.; Merry, Nona (IJMME-IJENS, 2014)
Selection of appropriate unique keyless grill locking system concept which complies with customer and technical requirements is one of the complicated decision making problem. In order to solve this problem, an idea selection based on the application of Analytic Hierarchy Process (AHP) is developed. This technique breaks down the multi-criteria into several levels and computes them using pairwise comparison matrices. The concepts of unique keyless grill locking system were evaluated using four main criteria: cost, quality, performance, and manufacturability. The results of the study indicate that the optimum concept is selected based on the highest score achieved from the overall ranking of each alternative concept.